This new hospital - LeBlang, Ted.; Greene, Penny; Marsh, Allen; Woodin, Dale.; American Society for Healthcare Engineering; HCTV.; Insight Media (Firm). ([Chicago, Ill.] American Society for Healthcare Engineering of the American Hospital Association New York, NY Insight Media [distributor], 2008)
Designed to assist hospitals as they build new facilities and renovate existing ones. The elements stressed on this DVD include: assembling the right team, reviewing scope and budgets, up front planning, and continued involvement of the project team.
Presented by HCTV (Healthcare Construction Television)
Ted LeBlang, Penny Greene, Allen Marsh, Dale Woodin.
DVD.
Keywords: Hospital buildings -- Design and construction; Hospital design and construction; Video discs